Targeting Trafficking in Drug Development (Handbook of Experimental Pharmacology, 2018)
Cellular trafficking is only recently identified as a site for therapeutic intervention. This book provides up to date information on the mechanism for exploiting this area for drug development as well as a clear understanding of the individual components of cellular trafficking. The authors are experts in their areas and the book features tables and figures that enable comparison and clear understanding.